Optimal Capacity Analysis Of Container Yard In Makassar New Port - Ningrum, Ainun Chandra Puspa; Idrus, Misliah; Ardianti, Andi (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
Indonesia is an island nation whose two-thirds of its territory is water and is located in a strategic location because it is on a cross of world trade routes; therefore, the role of the port as a marine transportation system is crucial in supporting economic growth. The stacking field used to serve container cargo is one of the main port facilities to store containers originating from ships or going to ships. A buildup field is needed to prevent the risk of ship delay, which results in decreased loading and unloading production and the time of ships and goods being ported for a prolonged time. Makassar New Port is the largest seaport in the Eastern Region of Indonesia. Located in the Makassar Strait, Makassar New Port holds a leading role in the distribution of goods equipped with loading and unloading facilities to and from the ship to the receiving warehouse. This study aims to analyze the fertilization field's capacity for both the operator and the user. The result of this study obtained for the short-term optimum cost Container Yard in Makassar New Port is IDR 1.687.795.482.144 with the width of field dimension is 530.000 m2 . While for the Medium Term optimum cost is IDR 1.688.202.882.750 with the width of field dimension is 530.000 m2 and Long Term is IDR 1.689.520.940.921 with the field dimension is 535.000 m2.Times